Influence of the organizational climate on job satisfaction of workers, Supte San Jorge Health Center, 2017 - Echevarria-Arratea, Clay (2019)
the present investigation analyzed and determined the level of influence of the organizational climate on the job satisfaction of the Internal Users of the Supte San Jorge Health Center, Rupa Rupa, Micronetwork of the Leoncio Prado Health Network, in which an investigation was applied of a non-experimental, descriptive, explanatory, transversal type of correlational design, the sample population was 30 workers, which has made up the unit of analysis; the Likert Scale Instrument for Organizational Climate and a Labor Satisfaction Questionnaire were applied, 83.4% of the workers expressed dissatisfaction with a low level of work climate, while 16.7% of the workers feel satisfied with a favorable work environment . The correlation between the global scores of organizational climate and job satisfaction was statistically significant, both in care staff (r = 0.523, p <0.001) and administrative staff (r = 0.468, p <0.001). The conclusions obtained were that the perception of a low organizational climate is associated with a higher level of job dissatisfaction among internal users.